The Support for the Elderly in Formal, Non‑formal and Informal Care Provision Based on Examples in England - Hołyst, Justyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The main aim of the article was to present three aspects of community care for the elderly in England: formal care which is provided by government, non‑formal which is private care as well as non‑governmental organisations (NGOs), informal care mostly provided by family members. Presentation of these three forms of support for the elderly was to highlight the importance of multidisciplinary co‑operation as the core value in creating an effective care package of an elderly person. Interdisciplinary approach in community care provision gives an elderly person opportunities to remain in his/her own home environment. The new way in functioning of social care tends to be called integrated care model where co‑operation and coordination of various tasks is essential. This article emphasises the importance of family member who provides care on a daily basis.